Fleksibilitas Penerapan Syariah Islam - Misbahuddin, Misbahuddin (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This article addresses the flexibility of shariah in human life. This is based on the assumption that Shariah cannot offer solution toward human affairs. It is also to counter argument that shariah is merely fit to prophethood situation. Consequently, shariah was believed as monotonovs and exlusive. This also leads to assume that Islam has no ability to solve Islamic affairs in the current context. In other words, Shariah is irrelevant in dealing with time and situation. Based on qualitative methodology, the author shows a number of elements on shariah which prove the ability of Shariah to solve human life affairs. The author, in this sense, lists qiyas, istihsan, and istislah as the means of generating product of Islamic law. In short, this article discusses shariah from different perpective focusing on Islamic jurisprudence. The author eventually come to conclude that there are many dimensions of shariah which illustrate that shariah can deal with the time as well as situation